BRUTE FORCE PASSWORD CRACKING DENGAN MENGGUNAKAN GRAPHIC PROCESSING POWER - Himawan Pramaditya (Jurnal Teknologi dan Manajemen Informatika, 2016)
Password created to secure something against access from unauthorized persons. The longer the password created increasingly long and complex with a view to improving safety. Graphic processing unit can be used as a suitable medium to guess a password combinations quickly. This was due to a combination of password guessing process is in accordance with the architecture of a graphics processing unit that typically consist of hundreds or thousands of simple processing cores per unit. With the rapid development of technology in the field of processing power, a process that used to guess a password might take decades can now be done in just a matter of hours.DOI: https://doi.org/10.26905/jtmi.v2i1.615